A questionnaire to determine nurses' knowledge of delirium and its risk factors - Hare, Malcolm; Wynaden, Dianne; McGowan, Sunita; Landsborough, Ian; Speed, Gaye (eContent Management, 2008)
Delirium is a frequent complication of hospital admission, especially among the elderly. It can have serious consequences in terms of morbidity, mortality and decreased quality of life. Nevertheless, an extensive literature review found that it is poorly recognised and poorly managed by medical and nursing staff.Although some researchers have found that education programs for nurses can improve outcomes for patients with delirium, no research assessing nurses' knowledge was found. The objective of this research was to determine nurses' level of knowledge regarding delirium and its risk factors. A questionnaire survey sent to nurses at a teaching hospital found that nurses? knowledge of delirium was generally inadequate, although one ward which had had inservice education attained better results. It is recommended that cognitive assessment in general and delirium in particular be incorporated into nursingeducation. Improved education could potentially lead to improved health outcomes and considerable cost savings.